Pengembangan Perangkat Pembelajaran dengan Model Direct Instruction Berbasis Digital Book Bagi Mahasiswa Slow Learner - Dian Ratnaningtyas Afifah; Fida Chasanatun; Sri Lestari; Wasilatul Murtafiah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Education for all is an important issue of concern in the world of education, including higher education. To accommodate this, higher education certainly needs to pay attention if there are students who experience special needs, especially regarding the absorption of lecture material. The aim of this research is to help students achieve the expected competencies in the English for Early Childhood course, especially for students who have special needs who are slow learners. The method used to develop learning media refers to Design Based Research from Technology Perspective. The research results show that through the Direct Instruction learning model based on digital books, it is easier for students to learn and practice how to provide English language stimulation to young children.